How macrophages respond to two-dimensional materials: a critical overview focusing on toxicity. Issue 4 (3rd April 2021) - Lin, Hazel; Song, Zhengmei; Bianco, Alberto
Abstract: With wider use of graphene-based materials and other two-dimensional (2 D) materials in various fields, including electronics, composites, biomedicine, etc., 2 D materials can trigger undesired effects at cellular, tissue and organ level. Macrophages can be found in many organs. They are one of the most important cells in the immune system and they are relevant in the study of nanomaterials as they phagocytose them. Nanomaterials have multi-faceted effects on phagocytic immune cells like macrophages, showing signs of inflammation in the form of pro-inflammatory cytokine or reactive oxidation species production, or upregulation of activation markers due to the presence of these foreign bodies. This review is catered to researchers interested in the potential impact and toxicity of 2 D materials, particularly in macrophages, focusing on few-layer graphene, graphene oxide, graphene quantum dots, as well as other promising 2 D materials containing molybdenum, manganese, boron, phosphorus and tungsten. We describe applications relevant to the growing area of 2 D materials research, and the possible risks of ions and molecules used in the production of these promising 2 D materials, or those produced by the degradation and dissolution of 2 D materials.